As Ciências Sociais no contexto das encruzilhadas do SUS - Cohn, Amélia (Saúde e Sociedade, 2022)
The acute crisis that plagues Brazil today causes the perplexity of the unexpected in the academic community. Especially after the experiences of democratic consolidation represented, although differently, by the governments of Fernando Henrique Cardoso, Lula, and Dilma. This historical setback was not in the scientific imaginary. The constant and recurrent aggressions to the development of the Brazilian National Health System (SUS) and the consolidation of constitutional precepts, in permanent construction since 1988.